Inverse Dynamic Game Methods for Identification of Cooperative System Behavior - Jairo Inga Charaja, Juan (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2021)
This work addresses inverse dynamic games, which generalize the inverse problem of optimal control, and where the aim is to identify cost functions based on observed optimal trajectories. The identified cost functions can describe individual behavior in cooperative systems, e.g. human behavior in human-machine haptic shared control scenarios.